Building and protecting business through intellectual property rights - Purwanto, Edy; Hidayaturrahman, Mohammad (Universitas Muhammadiyah Malang, 2021)
Pagerungan Besar is one of the villages in Sapeken District which has quite a good marine and agricultural product potential. MSME actors in Pagerungan Besar are currently starting to develop, but there are concerns about the large number of counterfeit products that can damage the brand or product image that has been grown up. This activity was aimed to provide understanding to MSME actors in Pagerungan Besar Village regarding Intellectual Property Rights.Â Activities carried out in the form of socialization and assistance. This method is the right way to solve the problems experienced by MSME actors in Pagerungan Besar. There was 30 MSME actor who attended the socialization and mentoring activities. The results of this activity indicate that there is a significant change in the respondent's understanding of intellectual property rights. Before the socialization, only 5 participants (15%) knew and had heard of IPR, but after the socialization, 30 participants (100%) already understood IPR. Furthermore, assistance efforts must be carried out until the MSME actors have the rights to the works they own, be it trademarks, copyrights and, other intellectual property rights.